Competition between prismatic and basal slip in hexagonal titanium–aluminum alloys with short-range order. Issue 6 (3rd June 2023) - Kwasniak, P.; Delannoy, S.; Prima, F.; Clouet, E.
Abstract : Plasticity of hexagonal titanium–aluminum alloys depends on the solute concentration and the order state of Al atoms. Development of short-range order (SRO) modifies Al strengthening and impacts the competition between prismatic and basal slip modes. Using ab initio calculations, we study the interaction of a screw dislocation with isolated Al atoms and Al pairs in an hcp Ti existing in short-range ordered Ti–Al alloys. Calculated activation energies reveal pronounced hardening caused by Al addition for both slip systems, which become competitive. This hardening is enhanced for Al pairs, resulting in a reduced plastic anisotropy of Ti–Al alloys with SRO. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: Short-range ordering is shown to impact plasticity in ahexagonal Ti–Al solid solution through ab initio modeling of dislocation interaction withsolute and pair of solute atoms.